Successful use of linezolid for refractory Mycobacterium abcessus infection: A case report - Teppei Inoue; Akihito Tsunoda; Eriko Nishimoto; Kohei Nishida; Yuka Komatsubara; Rintaro Onoe; Junko Saji; Masamichi Mineshita (Respiratory Medicine Case Reports, 2018)
A 51-year-old male patient was receiving treatment for Mycobacterium abscessus infection for approximately 10 years. However, as his condition gradually progressed to type II respiratory insufficiency, he was referred to our hospital, which was near his home. Computed tomography on his first visit revealed an abscess in the right lower lobe. Because respiratory insufficiency was evident, he was admitted the same day. We began treatment with meropenem, amikacin, and clarithromycin, but his symptoms did not improve. In accordance with the 2007 American Thoracic Society/Infectious Diseases Society of America statement, we administered linezolid, which resulted in gradual improvement in his physical status and imaging findings. Keywords: Nontuberculous mycobacterium, Mycobacterium abscessus, Linezolid